2017
DOI: 10.1016/j.fertnstert.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hodgkin or non-Hodgkin lymphoma and their treatments on sperm aneuploidy: a prospective study by the French CECOS network

Abstract: Lymphoma itself has consequences on sperm aneuploidy frequency before treatment. Moreover, lymphoma treatments have deleterious effects on sperm chromosomes related to treatment type and time since treatment. Patient counseling is essential concerning the transient but significant sperm aneuploidy induced by lymphoma and its treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 53 publications
2
37
3
Order By: Relevance
“…Thus, a multicenter prospective study assessing sperm aneuploidy in lymphoma patients demonstrated that ABVD and CHOP/MOPP-ABV (mechlorethamine, vincristine, procarbazine, prednisone-doxorubicin, bleomycin, vinblastine) treatments resulted in increased aneuploidy frequencies three months after the completion of the treatment. In patients treated with ABVD, aneuploidy rates returned to lower values than before treatment one or two years following the chemotherapy, whereas these rates were still relatively high until two years after in patients who received CHOP/MOPP-ABV [121].…”
Section: Sperm Nuclear Abnormalitiesmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, a multicenter prospective study assessing sperm aneuploidy in lymphoma patients demonstrated that ABVD and CHOP/MOPP-ABV (mechlorethamine, vincristine, procarbazine, prednisone-doxorubicin, bleomycin, vinblastine) treatments resulted in increased aneuploidy frequencies three months after the completion of the treatment. In patients treated with ABVD, aneuploidy rates returned to lower values than before treatment one or two years following the chemotherapy, whereas these rates were still relatively high until two years after in patients who received CHOP/MOPP-ABV [121].…”
Section: Sperm Nuclear Abnormalitiesmentioning
confidence: 84%
“…In addition, a raised frequency of chromosome 13 and 21 nullisomy has been observed in testicular cancer patients and Hodgkin's lymphoma patients 18 to 24 months after the chemotherapy initiation [120]. Most of studies using FISH analysis report a sexual chromosome disomy in patients after CHOP/MOPP-ABV, ABVD, or BEP regimen [115,120,121]. Close to 40% of testicular cancer patients did not recover normal sperm aneuploidy rates after treatment, and it would be advisable to postpone the parental project up to 24 months after more than two BEP chemotherapy cycles to prevent a potential risk of aneuploid conceptus [115].…”
Section: Sperm Nuclear Abnormalitiesmentioning
confidence: 99%
“…ABVD treatment also produced a transient high frequency of chromosomal alterations in spermatozoa of HL patients that decreased 3-18 months later [50,62]. In an interesting study, (Table 4).…”
Section: Impact Of Anticancer Therapy On Fertility and Germ Cell Genomentioning
confidence: 88%
“…The most aggressive treatment is MOPP since 90 to 100% of survivors have azoospermia [8,45,[48][49][50]. In contrast, ABVD is less toxic causing transient azoospermia in one-third of patients, and most of them recover sperm production [49][50][51] (Table 3). reported that damage "appeared to be not specific for chromosome pairs or regions to be involved in the structural exchanges", which may be interpreted as NCCA.…”
Section: Impact Of Anticancer Therapy On Fertility and Germ Cell Genomentioning
confidence: 99%
“…Genomic analyses of sperm samples are consistent with these results. FISH analysis of spermatozoa from patients given chemotherapy that lacked alkylating agents and/or with gonadal radiation doses of <1 Gy all showed no increase in aneuploidy (errors in chromosome number), at 1 year after treatment . In patients given chemotherapy that included alkylating agents or cisplatin, aneuploidy completely returned to pre‐treatment values 2 years after treatment .…”
Section: Absence Of Significant Induction Of Mutations In Human Stem mentioning
confidence: 98%